Rapid determination for fatigue parameters of AZ31B magnesium alloy based on evolution of temperature under high cyclic fatigue. (November 2014) - Zhang, H. X.; Guo, S. F.; Yan, Z. F.; Liu, X. Q.; Wu, G. H.; Pei, F. F.; Wang, W. X.; Wang, K.
Abstract : Based on the infrared thermography method, experiments are carried out to investigate the evolution of temperature field of the extruded AZ31B magnesium alloy specimens under high cyclic fatigue load. The experimental results show that the superficial temperature of specimen under cyclic fatigue load changes with the number of cycles. According to the characteristics of surface temperature change, we propose a formula to calculate the residual fatigue life using energy approach. The proposed formula to assess the fatigue parameters (fatigue limit, residual fatigue life, fatigue life and S–N curve) achieves good results for AZ31B magnesium alloy. Furthermore, the fatigue limits (Δ σ eSN = 90·3 MPa) derived from the traditional method through 10 7 cycles were compared with the values predicted by the infrared thermographic method (Δ σ eTM = 87·3 MPa) and the energy approach (Δ σ eΦ = 86·2 MPa), and the comparison results of percentage differences are 3·3 and 4·5% respectively.